Investigations on a new engine concept for small hydrogen power generation units using LOHCs - Schumacher, Moritz; Mederer, Thomas; Wensing, Michael (SAE Technical Papers, 2013)
New energy scenarios for decentralised stationary energy supply based on Liquid Organic Hydrogen Carriers (LOHC) offer an attractive application for hydrogen engines and are a reason why hydrogen engines become topical again. Since hydrogen stored in LOHCs is released under ambient pressure and temperatures of over 200°C, compression and cooling of the hydrogen is needed, lowering the system's overall efficiency. Direct injection of hydrogen is advantageous due to its low volumetric energy density and the tendency towards pre-ignition. The development objective is an injection and combustion strategy for an engine in the performance category below 15 kW and the described fuel supply scenario. Therefore, an one dimensional simulation model of the engine and the hydrogen supplying compressor was built. The simulation results show a large influence of the injection pressure on engine efficiency due to the hydrogen supplying compressor. For the studies presented here an engine with an extended expansion was built for an increased utilisation of exhaust gas enthalpy. The extended expansion was also implemented in the one dimensional simulation model. First results show enhanced indicated efficiency under high load conditions. Furthermore, preliminary investigations on hydrogen combustion have been carried out using an optically accessible hydrogen engine. Laser-induced fluorescence was applied to investigate the effect of varied injection pressures and timings on the processes of injection, mixture formation and combustion. The end-of-injection timing variation showed that approx. 90 °CA are necessary to generate a homogeneous mixture in the combustion chamber which limits the injection timing for homogeneous combustion concepts. Copyright © 2013 SAE International and Copyright © 2013 KSAE.
Created from Fastlane, Scopus look-up